2006
DOI: 10.1203/01.pdr.0000245912.78078.d5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Flax Oil During Pregnancy and Lactation Retards Disease Progression in Rat Offspring With Inherited Kidney Disease

Abstract: Dietary flax oil (FO) retards disease progression in growing or adult animal models of kidney disease. To determine whether dietary flax oil during the perinatal period would alter renal disease progression in offspring, Han-SPRD-cy rats with inherited cystic kidney disease were given diets with either 7% FO or corn oil (CO), throughout pregnancy and lactation. At 3 wk of age, offspring were then given either the same or the alternate diet for 7 wk. Rats given FO during the maternal period had 15% less renal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Various models have been developed for generating experimental PPA, including abrasion, local excision of the peritoneum, ischemic injury, placement of a foreign body in the peritoneal cavity (e.g., talcum powder), thermal injury, and bacterial contamination [20][21][22][23][24][25][26]. We have utilized an abrasion model, due to its ability to mimic mechanical trauma, which can occur after laparotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various models have been developed for generating experimental PPA, including abrasion, local excision of the peritoneum, ischemic injury, placement of a foreign body in the peritoneal cavity (e.g., talcum powder), thermal injury, and bacterial contamination [20][21][22][23][24][25][26]. We have utilized an abrasion model, due to its ability to mimic mechanical trauma, which can occur after laparotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary flax oil retard kidney disease progression when initiated in early and also late stages of disease in several experimental models [23][24][25][26]. Flaxseed meal is effective in preventing colon tumor development when compared with dietary corn meal [27].…”
Section: Discussionmentioning
confidence: 99%
“…MGV was calculated by measuring the maximum diameter of each glomerular tuft using Image-Pro Plus Software 6.0 measurement tools. The diameters (μm) were converted to MGV using the following equations: mean glomerular area (MGA)=πr 2 and MGV=1.25 (MGA) 3/2 , as developed by Weibel [60] and described previously [61]. To determine glomerular fibrosis, 25 randomly selected glomeruli were examined by light microscopy using a 40× objective to examine one glomerulus per slide.…”
Section: Histological Analysesmentioning
confidence: 99%
“…Adult (age 2 months) male Han:SPRD-cy rats in the advanced stage of ADPKD fed 16% kcal ALA-rich flaxseed oil for 4 months showed no significant effect on renal cyst volume and interstitial fibrosis compared to rats fed LNA-rich corn oil. On the other hand, Hans:SPRD-cy rats exposure to ALA by providing rat dams 16% kcal flaxseed through pregnancy and lactation resulted in offspring with less renal cyst growth, proliferation, oxidation, and increased renal function compared to offspring exposed to flaxseed oil starting at weaning [32] ( Table 1). The study results indicated that early diet intervention was beneficial for attenuating PKD development and progression.…”
Section: Authorsmentioning
confidence: 99%